IMPLEMENTASI KEBIJAKAN PERDA PROVINSI DIY NOMOR 13 TAHUN 2022 SEBAGAI UPAYA PEMENUHAN HAK PENDERITA GANGGUAN JIWA DI KABUPATEN SLEMAN - Tania Latifa Zahra; Hanantyo Sri Nugroho (Jurnal Academia Praja, 2025)
This study analyzes the implementation of the Yogyakarta Special Region Provincial Regulation Number 13 of 2022 concerning Mental Health Services in Sleman Regency, focusing on fulfilling the rights of People with Mental Disorders. The high number of cases of mental disorders and social stigma are the main reasons. Using a descriptive qualitative method with the theoretical framework of George C. Edwards III, the study examines four factors: communication, resources, disposition, and bureaucratic structure. The findings indicate: (1) Inter-agency communication (Social Services, Health, Satpol PP) is effective, but public communication is weak so that stigma remains dominant. (2) District resources are adequate in terms of budget and facilities, but rely on limited capacity provincial rehabilitation centers. (3) The disposition of highly committed apparatus is hampered by the low readiness of families to accept People with Mental Disorders, which causes repeated treatment cycles. (4) The bureaucratic structure has a clear flow in the district, hampered by the absence of village technical instructions and fragmentation of authority. Despite bureaucratic commitment, implementation is hampered by social stigma, resource dependence, and low family readiness. Recommendations include strengthening community-based anti-stigma campaigns, developing family empowerment programs, developing village technical guidelines, and advocating for capacity building in rehabilitation facilities.